SUPERVISI KLINIS MODEL PROCTOR DALAM PENINGKATAN KUALITAS PERAWATAN SELAMA PROSEDUR INTRAVENA - Setiawan, Herry; Hartiti, Tri; Rofi'i, Muhammad (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2018)
High phlebitis events reflected low quality of nursing care in terms of infection prevention and control.High phlebitis caused by a biological factor of treatment during an intravenous procedure. Thequality of care during intravenous procedures has influenced by the ability of the supervisor toperform clinical supervision. The purpose of this research is to know the influence of clinicalsupervision Proctor model on the quality of treatment during intravenous procedure at GeneralHospital Banjarmasin. The research method used quasy experimental with pre-post research designwith control group with total sample 68 responden taken with sample technique non probabilitysampling with the inclusion criteria of nurses who work as asociate nurses divided into group ofintervention and control. The results obtained in this study were the influence of clinical supervision ofProctor Model on the quality of care during intravenous procedure with p = <0.0001 with α = 0,05.There is an influence of the Proctor Model's clinical supervision on the quality of care during theintravenous procedure at General Hospital Banjarmasin.